Training on making digital brochures as an online promotion strategy for MSME products - Hera Febria Mavilinda; Nofiawaty Nofiawaty; Akhmad Nazaruddin; Lina Dameria Siregar (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Micro, small and medium enterprises (MSMEs) are one of the sectors that are essential pillars in the recovery of the Indonesian economy after the COVID-19 pandemic outbreak in early 2020. Through the Ministry of Cooperatives and SMEs, the Indonesian government is trying to make a transformative recovery to revive MSMEs after the pandemic by bringing MSMEs into the digital ecosystem. The first step to enter the digital ecosystem is to design an online promotion strategy. Digital brochures are a form of online promotional media that can be an alternative for MSMEs to market and sell their products in an interactive and interesting way. The purpose of community service is to support government programs in the transformative recovery of MSMEs by providing training and assistance in making digital brochures for MSMEs in Muara Penimbung Ilir Village using the Canva application. The participants consisted of 25 MSMEs. The method of implemention community service activities is carried out offline through presentation, tutorials and interactive discussions. The results showed that 95% of the participants had understood the steps in making digital brochures. In addition, they are able to make their own digital brochures using the Canva application to market their products online.